Perceptions of Using ChatGPT’s Real-Time Feedback to Enhance EFL Speaking Skills - Abdul Syahid; Triono Budi Nugroho; Nor Azizah Riana (CV. Ulil Albab Corp, 2024)
This study explores the personal experiences of EFL students using ChatGPT to strengthen their speaking skills, especially with real-time feedback. As AI tools like ChatGPT become an integral part of modern education, this research takes a qualitative approach to understand how students truly feel about using this technology. Through in-depth interviews and thematic analysis, we listened to students share how ChatGPT’s instant, interactive feedback helped them gain confidence, improve pronunciation, and speak more fluently. Many described it as a supportive companion in their language-learning journey, making practice sessions feel natural and engaging. While some students faced minor challenges, most appreciated how ChatGPT adapted to their unique needs, creating a safe and encouraging space for practice. This study shows the potential of AI tools like ChatGPT to bring something new and meaningful to language learning, supporting students in ways that go beyond traditional classrooms